Characterisation of serratia spp. from aquaculture environment and river water - Yap, Mui Lan (Universiti Malaysia Sarawak, (UNIMAS), 2013)
Serratia spp. is one of the significant human pathogen. Some Serratia spp. especially Serratia marcescens contain a lot of human clinical infection history as well as interesting taxonomic, military experimentation and medical experiment. Currently, Serratia marcescens and Serratia liquefaciens have been isolated as causative agents of numerous outbreaks and opportunistic infections. As the species appear to be common environmental organisms, large number of nosocomial infections due to these bacteria can be explained. Thus, molecular characterization of several Serratia spp. become the main objective of this research as an approach to gain better identification and characterisation of various of Serratia spp. In this study, antibiotic susceptibility and genetic diversity of Serratia spp. isolated from aquaculture environment and river water of Rayu river were determined. The levels of resistance of the Serratia isolates towards nineteen antibiotics were tested. These isolates displayed resistance towards most of the antibiotics tested but the level of resistance vary among the species. Genetic characterization of Serratia spp. were carried out by using GTGs-PCR which clustered the Serratia isolates into three groups based on DNA fingerprinting by using Paleontologi statistic software. The results of this study suggest that the Serratia isolates from aquaculture environment and river water derived a mixture of sensitive and resistant strains with diverse genetic contents.